A study on analysis of marine and land alienation at Sabah / Aidatul Jannah Suhaimi - Suhaimi, Aidatul Jannah (2021)
The introduction of the marine cadastre in Malaysia is still in its infancy even up to date compared to other countries such as Australia, United States and Canada where the country has already been approaching with the introduction of marine cadastre in advance of us. The concept of marine cadastre in Malaysia is only given to certain marine agencies but not all agencies related to other sectors in marine will be given to the concept of marine cadastre. This is because not all marine stakeholders come to the awareness of the marine cadastre and are still blurred by the definition of marine cadastre in the Malaysian environment as well as the lack of legislation to implement it. In Malaysia, the use of the National Land Code 1965 is for land cadastre purposes but it does not cover marine situations. As well as the state of Sabah, the use of the Land Ordinance Sabah also ineffective to marine legal but more to on land cadastre matter but not to marine cadastral. Besides, in Sabah also has ownership of marine land but is categorized as land ownership. Furthermore, laws and regulations implemented in Malaysia for marine areas are ineffective due to lack of enforcement. Besides. This research was carried out to analysis of marine and land alienation procedure at Sabah. In addition, the objective is to identify the concept of marine and land alienation practice in Sabah and Peninsular, to study/view the procedure of flowchart of the process acquiring marine land alienation in Sabah. And lastly to compare and contrast the flowchart of the process in acquiring marine land alienation in Sabah with Peninsular Malaysia. The method that used in this research study is using descriptive method. There are three methods used for data collection in this study such as Questionnaire, Discussion and interview and research library research.